PAPARAN RISIKO DARI KESELAMATAN JALAN DI INDONESIA BERDASARKAN FATALITAS KECELAKAAN - Anastasia Caroline Sutandi (Jurnal Jalan-Jembatan, 2022)
Numbers and fatality of casualties in Indonesia is a very serious problem that has to be solved as soon as possible. Data shows that 3 or 4 casualties die every 12 accidents per hour. The high risk occurs because of many factors i.e. humans, condition of road, vehicle, environment, technology, and weather that can be explained with Risk Exposure. The aims of this study are to determine the value of Risk Exposure in order to improve road safety in Indonesia based on accident fatality and then propose recommendations in order to reduce the number and fatality of the accident risk. Complete, accurate, and up to date data is collected from Korps Lalu Lintas Polri, 2019 and Statistics Central Bureau in year 2010-2019 in all provinces in Indonesia. Data from year 2010 up to year 2019 can be considered as a normal data, whereas data during pandemic conditions can be assumed as an up normal data because of many traffic policies applied as need at that time. Descriptive statistics indicated that Risk Exposure Value (REV) based on accident fatality to population number, vehicle number, driving license ownership, and various roads surface pavement conditions increase every year. From the REV, then the practice actions that have to be done soon are education to the divers, implementation of road furniture, and step by step installation of ITS as needed. The results of this study are important because the study reviews from another point of view rather than that most accidents are caused by human error and can then be used as a basis for real follow-up in the field. Key words: risk exposure, risk exposure value, road safety, Indonesia